2013
DOI: 10.2466/25.29.pms.117x31z4
|View full text |Cite
|
Sign up to set email alerts
|

Relations between BMI, Body Mass and Height, and Sports Competence among Participants of the 2010 Winter Olympic Games: Does Sport Metabolic Demand Differentiate?

Abstract: This study characterizes the athletes participating in the 2010 Winter Olympic Games in terms of body height, body mass and BMI. The studied sample consisted of athletes in the top 20 places of each of 14 sports disciplines (1460 cases). Data on the athletes' age, height, body mass, and sports specialization were obtained from the Olympic Games' official website and from the International Ski Federation. The sampled athletes were grouped according to the predominant type of energy metabolism during competition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Their psychological characteristics and tactical knowledge have to be very advanced so they can meet requirements set by this sport discipline and handle the stress. Athletes somatic variables such as body height, body weight, body mass index (BMI) or% body fat have a considerable influence on training strategy, as they can affect the technique and tactics for competition and athlete's specialization within a given discipline [ 20 – 22 ]. Based on the obtained results, with regard to body composition, significantly lower% body 13.17% was found in G1 group of hockey players than in the G2 16.53%.…”
Section: Discussionmentioning
confidence: 99%
“…Their psychological characteristics and tactical knowledge have to be very advanced so they can meet requirements set by this sport discipline and handle the stress. Athletes somatic variables such as body height, body weight, body mass index (BMI) or% body fat have a considerable influence on training strategy, as they can affect the technique and tactics for competition and athlete's specialization within a given discipline [ 20 – 22 ]. Based on the obtained results, with regard to body composition, significantly lower% body 13.17% was found in G1 group of hockey players than in the G2 16.53%.…”
Section: Discussionmentioning
confidence: 99%
“…Ice hockey is a very complex team game, the final result of which depends on various factors [30, 32]. Most important are the player's skills in skating, an activity involving maneuverers such as starts, accelerations, sprints, rapid changes in skating directions or braking.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum blood lactate for men athletes seem to be similar to the elite alpine skiers (13.69 ± 2.06 mmol/L) (28). The above findings suggest that the skill-based snowboarding athletes have a high anaerobic nonlactic acid energy supply capacity (33) and the speed-based snowboarding athletes have a high glycolytic capacity (27). However, Żebrowska et al (44) found that the maximum blood lactate during incremental load testing in elite alpine snowboarding athletes were not significantly different from untrained individuals.…”
Section: Resultsmentioning
confidence: 93%